Improvements in Outcomes and Cost After Adult Spinal Deformity Corrective Surgery Between 2008 and 2019. Issue 3 (1st February 2023) - Passias, Peter G.; Kummer, Nicholas; Imbo, Bailey; Lafage, Virginie; Lafage, Renaud; Smith, Justin S.; Line, Breton; Vira, Shaleen; Schoenfeld, Andrew J.; Gum, Jeffrey L.; Daniels, Alan H.; Klineberg, Eric O.; et al.
Abstract : Study Design: A retrospective cohort study. Objective: To assess whether patient outcomes and cost-effectiveness of adult spinal deformity (ASD) surgery have improved over the past decade. Background: Surgery for ASD is an effective intervention, but one that is also associated with large initial healthcare expenditures. Changes in the cost profile for ASD surgery over the last decade has not been evaluated previously. Materials and Methods: ASD patients who received surgery between 2008 and 2019 were included. Analysis of covariance was used to establish estimated marginal means for outcome measures [complication rates, reoperations, health-related quality of life, total cost, utility gained, quality adjusted life years (QALYs), cost-efficiency (cost per QALY)] by year of initial surgery. Cost was calculated using the PearlDiver database and represented national averages of Medicare reimbursement for services within a 30-day window including length of stay and death differentiated by complication/comorbidity, revision, and surgical approach. Internal cost data was based on individual patient diagnosis-related group codes, limiting revisions to those within two years (2Y) of the initial surgery. Cost per QALY over the course of 2008–2019 were then calculated. Results: There were 1236 patients included. There was an overall decrease in rates of any complication (0.78 vs . 0.61), any reoperation (0.25 vs . 0.10), and minor complication (0.54 vs . 0.37) between 2009 and 2018 (all P <0.05). National average 2Y cost decreased at an annual rate of $3194 ( R 2 =0.6602), 2Y utility gained increased at an annual rate of 0.0041 ( R 2 =0.57), 2Y QALYs gained increased annually by 0.008 ( R 2 =0.57), and 2Y cost per QALY decreased per year by $39, 953 ( R 2 =0.6778). Conclusion: Between 2008 and 2019, rates of complications have decreased concurrently with improvements in patient reported outcomes, resulting in improved cost effectiveness according to national Medicare average and individual patient cost data. The value of ASD surgery has improved substantially over the course of the last decade.